2019
DOI: 10.1097/brs.0000000000002940
|View full text |Cite
|
Sign up to set email alerts
|

Does Symmetric Thoracic Fusion Make a Difference in Lenke 1 A/B AIS Patients?

Abstract: Study Design. A retrospective study. Objective. The aim of this study was to compare the long-term outcomes of correction surgery for Lenke 1 A/B scoliosis among those with symmetric fusion (SF), upper-dominant fusion (UF), and lower-dominant fusion (LF) in adolescent idiopathic scoliosis (AIS). Summary of Background Data. Symmetric fusion, defined as equal number of vertebral levels included in instrumented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Our previous study compared the long-term outcome of correction surgery for Lenke 1 A/B AIS among those with symmetric fusion (SF), upper-dominant fusion (UF: more vertebrae was fused above the apex), and lower dominant fusion (LF: more vertebrae was fused below the apex). 16 Significant higher incidence of adding-on was found in UF compared to SF and LF. Our current finding was consistent with previous study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our previous study compared the long-term outcome of correction surgery for Lenke 1 A/B AIS among those with symmetric fusion (SF), upper-dominant fusion (UF: more vertebrae was fused above the apex), and lower dominant fusion (LF: more vertebrae was fused below the apex). 16 Significant higher incidence of adding-on was found in UF compared to SF and LF. Our current finding was consistent with previous study.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, long thoracic curve with low apex location was a risk factor for distal adding-on when stopping distally at LSTV-1. Our previous study compared the long-term outcome of correction surgery for Lenke 1 A/B AIS among those with symmetric fusion (SF), upper-dominant fusion (UF: more vertebrae was fused above the apex), and lower dominant fusion (LF: more vertebrae was fused below the apex) 16 . Significant higher incidence of adding-on was found in UF compared to SF and LF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study defined 2 cm as the threshold value of CI, which was based on the work of Zhao et al 26 and Hwang et al 27 The incidence of postoperative CI among patients with EOS (18%) was similar to that of young adolescent patients (range 9.1%-20.8%), [7][8][9][10] but slightly lower than those of patients with degenerative lumbar scoliosis (range 25.6%-31.6%). [3][4][5][6] Concerning the effect of definitive spinal fusion on CI during distraction periods, the current study noted that patients with CI showed only a small improvement in coronal balance and continued to be diagnosed with this complication at the latest follow-up.…”
Section: Discussionmentioning
confidence: 92%